1979
DOI: 10.1007/bf02277985
|View full text |Cite
|
Sign up to set email alerts
|

Continuous underwater light measurement near Helgoland (North Sea) and its significance for characteristic light limits in the sublittoral region

Abstract: Underwater irradiance was measured at intervals of 20 min for one year at 2 water depths (2.5 and 3.5 m below M.L.W.S.) and in 3 spectral regions in the sublittoral region of the rocky island of Helgoland. Data are presented for spectral and total irradiance at water depths ranging from 2 to 15 m (below M.L.W.S.). 90 % of the total annual light reaching sublittoral habitats is received during the period from April to September, when Jerlov water type 7 (occasionally water type 5) dominates. During the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
2

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(80 citation statements)
references
References 21 publications
4
72
2
Order By: Relevance
“…corresponded to roughly 4% of PAR at sea level. This value is higher than the estimations by Kain (1971) and Kain et al (1976) (1.0 to 1.9% of PAR at sea level) and by Lüning & Dring (1979), near Helgoland (North Sea), where Laminaria hyperborea lived to depths of 8 m, receiving 0.7% of visible surface irradiance. Kelps collected in the present study were observed to ca.…”
contrasting
confidence: 56%
“…corresponded to roughly 4% of PAR at sea level. This value is higher than the estimations by Kain (1971) and Kain et al (1976) (1.0 to 1.9% of PAR at sea level) and by Lüning & Dring (1979), near Helgoland (North Sea), where Laminaria hyperborea lived to depths of 8 m, receiving 0.7% of visible surface irradiance. Kelps collected in the present study were observed to ca.…”
contrasting
confidence: 56%
“…Culture experience with unicellular algae indicates that representatives of all major algal groups can be cultivated at photon fluence rates of the order of 1 #mol m-2s -1 (Geider et al, 1985). The minimum level of 0"1 #tool m-2s -1 at 12 h light per day allowing first microscopic hints of growth after 15 weeks of cultivation in the filamentous red alga Audouinella daviesii (Tables 2, 3) converts to l'6mol photons m-2year -I. Liining & Dring (1979) calculated an annual quantum input of 6 tool photons m-2year -1 for the deepest-occurring, macroscopically visible coralline crusts near Helgoland -of a similar order as the present result.…”
Section: Discussionmentioning
confidence: 99%
“…), which are strongly affected by both light quality and intensity (Liining 1980). However, most of the studies designed to address the relationship between the light environment and macroalgal zonation have been focused on the large sporophytic stages (Liining 1979, Luning & Dring 1979, whereas 'E-mail: cwienckeOa\v1-bremerhaven.de "Present address: Foundation Alfred Wegener Institute, Section Coastal Ecology, Hafenstrasse 43, 25992 List/Sylt, Germany physiological adaptations to depth of motile zoospores have been largely overlooked (Kain 1964, Luning 1980, Amsler & Neushul 1991. For example, some evidence indicates that photosynthetic rates of kelp zoospores are low, just balancing respiration (Kain 1964), and carbon assimilation of zoospores might condition their viability and dispersal capacity (Amsler & Neushul 1991).…”
Section: Introductionmentioning
confidence: 99%